Human Service Organization (HSO) Study of the Indonesian Red Cross (PMI) in Health and Community Welfare Services in Bandung City - Yuliyantini, Yuliyantini; Suhara, Ero (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is motivated by the importance of the HSO's task in improving social welfare efforts or providing social welfare services to individuals, groups, families and communities who experience social problems or as a